BALANCED DEVELOPMENT STRATEGIES IN THE ERA OF DIGITAL TRANSFORMATION: OPTIMIZATION OF PROJECT ANALYSIS THROUGH THE APPLICATION OF AI IN MARKETING COMMUNICATIONS - Maslak, Olga; Maslak, Mariya; Yakovenko, Yaroslava; Hryshko, Natalya (Current Problems of Sustainable Development, 2026)
The article investigates the economic efficiency of hybrid IT project management methodologies  through the prism of integrating artificial intelligence (AI) systems into marketing communications. Statistical data from the global market and the Ukrainian IT sector for 2023–2025 are analyzed. It is revealed that the increasing technological complexity of products and high market dynamics require a transition from traditional management systems to adaptive, data-driven ones. It is proven that the use of hybrid methodologies in synergy with AI tools for analyzing marketing communications allows for predictive adjustment of product requirements, increasing the probability of successful project completion and customer satisfaction. The role of this integration in ensuring the balanced development of the IT sector according to ESG criteria is substantiated, optimizing resources, minimizing the environmental footprint, and preventing team burnout through more accurate workload forecasting.
Keywords: digitalization; adaptive management systems; artificial intelligence; marketing communications; digital marketing; balanced (sustainable) development; ESG; project analysis; innovative development; digital transformations; IT sector